An EFL Teacher’s Problems and Solutions in Teaching Writing at Grade XII - Wardana, Riza Fikri; Fajarina, Maskhurin (Teaching English as Foreign Language, Literature and Linguistics, 2025)
This research aims to find out problems that the teacher encountered in teaching writing and the ssolutions he employed to overcome these challenges. This research was conducted in class XI D, XI E, XI F, and XI N on 20-26 February 2025. Before doing the research, the researchers prepared observations and interview used to know teacher’s problems and solutions in teaching writing. In this research, the researcher used descriptive qualitative design and to collected data, the researcher used Observation and Interview. To analyze the data, the researcher used a-three-step theory of qualitative data analysis consisting of condensation the data, displaying the data drawing and verifying the conclusion. The result of this research is that there are 4 EFL teacher problems and 4 solutions to overcome them. These problems are that the teacher faced students with limited of vocabularies, poor grammar, having difficulty developing ideas, and dealing with students who have low motivation in learning English. To overcome the problems, namely collecting and memorizing vocabulary, having exercises of English writing, practicing writing, and giving good evidence for students. Hopefully, this research can be a reference for future researchers as well as English teachers when teaching writing.